Effect of viscous dissipation term on a fluid between two moving parallel plates (2018)
The fully developed laminar heat transfer of a Newtonian fluid flowing between two parallel plates where the bottom plate is fixed and the top plate is moving in an axial direction at constant speed was analyzed taking into account the iscous dissipation of the flowing fluid. Applying the velocity profile obtained for the plane Coutte-Poiseuille laminar flow, the energy equation with the viscous dissipation term was exactly solved for the boundary conditions of constant wall heat flux at one wall with the other insulated. Special attention is given to the shear produced by the movable top plate over and above the viscous dissipation due to internal fluid friction. The reason behind the behaviour exhibits by the temperature profile obtained at different velocities can be attributed to the effect of viscous dissipation coming into play due to the shear stress within the fluid layer induced by the movement of the upper plate